MANAJEMEN LABA: PERILAKU MANAJEMEN OPPORTUNISTIC ATAU REALISTIC ? - Wijana Asmara Putra, I Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
Earnings management is a still attractive issue. It is often associatedwith negative behavior conducted by management for its own interest. In fact,it also has different side to be examined. There is another motivation to do so,such as to improve the company’s operation. This literature study aims toreview management motivation of doing earnings management, whetheropportunistic or realistic. What conflict that earnings management brings,what pro and cons about it, what would happen if earnings is not managed,whether the company would be better off or worse off.
Keywords: earnings, management, opportunistic, realistic behavior